Gratitud y bienestar desde la perspectiva de niños y las niñas de edad escolar en Bogotá (2020)
This study is framed within the project Positive design of a program to promote gratitude in school-age children led by professors Sonia Carrillo ávila, Yvonne Gomez Maquet and Gordon Dunstan Ingram from the department of psychology at the University of Los Andes. For this study, data collected in 2019 for Phase 1 of said project was used, which is funded by The Templeton World Charity Foundation. The purpose of this study was to explore the relationship between the elements of gratitude identified by fifth-grade children and aspects of their wellbeing. The sample consisted of 38 children from 3 schools in Bogotá, Colombia. A model of well iii -being created from the perspective of children was used in order to explore different experiences of gratitude reported by the participants.